بیرکردنەوەی ناعەقاڵنی وپەیوەندی بەڕازیبوون لەژیان لەالی بەڕێوەبەران و یاریدەدەرانی باخچەی مندااڵن - خالد, حسن فخرالدین; قادرحمە, ڕێناس (Sulaimani Journal for Humanities, 2022)
The aim of this research is to know the level of illogical thinking and satisfaction of life to principals and assistants of kindergartens and knowing the relationship between illogical thinking of satisfaction of life and also knowing the level of illogical thinking of acceptance of life according to both variables of age and academic degree. To validate these aims, the research implemented the descriptive method and the tools of the research consisted of two tools to both variables of illogical thinking and acceptance of life. The tool of illogical thinking consisted of (44) elements and the tool of life satisfaction consisted of (55) elements. After ensuring the validity and reliability of the instrument, the data collection method was executed onto the sample of the research which consisted of all of the principals and assistants of the kindergartens in the center of Sulaimani City, that is, (35) principals and (30) assistants. To analyze and interpret the results of the collected data, the researcher utilized (SPSS) program to interpret the data. It was concluded that illogical thinking to kindergarten principals and assistants is generally low and the level of satisfaction of life to kindergarten principals and assistants is generally high. Moreover, no significant, evidential, and statistical difference is found between the median of the results of kindergarten principals and assistants concerning the dimension of illogical thinking and satisfaction of life depending on both variables of age and academic degree.